Fenomena Temper Embrittlement Pada Baja Martensitik AISI 410 Untuk Aplikasi Stem Gate Valve 20” Class 150 Grade WCB [Temper Embrittlement Phenomena of AISI 410 Martensitic Steel for Stem Gate Valve 20” Class 150 Grade WCB ] - Galih Senopati; Cahya Sutowo; Efendi Mabruri (National Research and Innovation Agency (BRIN), 2016)
Temper embrittlement is a phenomenon that will decrease the toughness of steel due to tempering process at a certain temperature range. This phenomenon has been found in martensitic steel. This research is investigated the failure in stem gate valve of crude oil pipeline system. The stem gate valve material is made of stainless steel AISI 410. Several examinations were done to study cause of failure in stem gate valve such as visual inspection, chemical composition test using OES (optical emission spectrometer) and EDS (energy dispersive spectrometry), metallography observation by using optical microscopy (OM) and SEM (scanning electron microscopy), fractography using SEM, and Rockwell hardness test. Chemical composition test result on stem gate valve showed 13,65-13,67 wt.% Cr. The content of Cr in stem material is out from the required composition of AISI standard with the requirement of Cr amount 13,5 wt.%. Fractography result on the surface of failure stem area by SEM was observed intergranular crack followed by secondary crack. Its indicated that stem gate valve failure was caused by temper embrittlement due to tempering process.AbstrakTemper embrittlement merupakan fenomena penurunan kekuatan dari material baja yang disebabkan oleh proses tempering pada rentang temperatur tertentu. Beberapa kasus temper embrittlement ditemukan pada baja martensitik. Pada studi kali ini dilakukan pengamatan terhadap stem gate valve pada sistem perpipaan minyak mentah yang mengalami patah. Stem gate valve tersebut terbuat dari baja tahan karat martensitik tipe AISI 410. Kemudian dilakukan beberapa pengujian untuk mengetahui proses terjadinya patah pada stem gate valve yang meliputi pemeriksaan visual, analisa komposisi kimia dengan OES (optical emission spectrometer) dan EDS (energy dispersive spectrometry), pengamatan metalografi dengan OM (optical microscopy) dan SEM (scanning electron microscopy), fraktografi dengan SEM, serta uji keras Rockwell. Hasil pemeriksaan pada stem gate valve menunjukkan komposisi Cr adalah 13,65-13,67 % berat atau melebihi batas atas standar AISI 410 yaitu 13,5 %berat. Dari pengamatan struktur mikro diketahui material stem gate valve dalam kondisi telah dilakukan proses tempering dan teramati adanya secondary crack. Dari pengamatan fraktografi diketahui jenis retakan pada permukaan stem yang patah adalah retakan antar butir (intergranular crack) yang mengindikasikan terjadinya proses temper embrittlement pada saat proses tempering material stem gate valve.